Is Routine Histopathology Of Gall Bladder After Laparoscopic Cholecystectomy Needed?: A Local Perspective - Ali Mohammad Khatri; Ghani Haider; Aliya Hasnain; Muhammad Umer Ahmed; Nazia Mumtaz; Wajahat Hussain Wasty; Aruna P .Dawani (ziauddin University, 2024)
Background: Laparoscopic Cholecystectomy is one of the most commonly performed routine operation in modern general surgery. All surgical specimens are routinely sent for histopathology. A wide spectrum of variations is seen under the microscope. Rarely, carcinoma is discovered on histopathological examination. The purpose of the article was to identify and elaborate the major histopathological findings of gallbladder after laparoscopic cholecystectomy in a tertiary health care hospital in Pakistan. Methods: This was a retrospective study and included histopathological specimens of gall bladder after cholecystectomy from February 2004 to April 2013. Data was analysed using MS Excel and SPSS 19.0. Results: Total number of cases: 8376, Chronic Cholecystitis: 7705, Acute or chronic cholecystitis with empyema, mucocele or gangrene: 554, Adenocarcinoma: 91, Adenomatous polyp: 3, Squamous cell carcinoma: 5, Papillary carcinoma: 3, Clear cell carcinoma: 4, Adenosquamous carcinoma: 2, Xanthogranulomatous changes: 54, Dysplasia: 13 and Cholesterosis: 1050. Conclusion: Considering the evidence from our study and the evidence from the literature reviewed, it can be concluded that prevalence of all kinds of gall bladder disease, benign or malignant including carcinoma is no different from the rest of the world. Routine histopathology of gall bladder can be omitted without compromising patient safety as proven and practiced by many centers across the globe. Key Words: Histopathology, Gallbladder, Laparoscopic Cholecystectomy